Interface electronic properties of eterojunctions based on nanocrystalline silicon - Kaganovich, E.B.; Kirillova, S.I.; Manoilov, E.G.; Primachenko, V.E.; Svechnikov, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
For investigations of electronic properties of heterojunctions nanocrystalline Si film (nc-Si)/ monocrystalline Si (c-Si) the technique of temperature dependencies of surface photovoltage was used. Two types of samples fabricated by laser ablation of c-Si target with deposition of nc-Si films onto substrates situated at a distance from the target and onto the plane of target were studied. The temperature dependencies of concentration of charge carriers captured in the traps in the heterojunction interface, and of distribution of density of surface electron states on energy were calculated. The connections between conditions of heterojunction fabrication and their electronic properties are clarified.